2005
DOI: 10.1111/j.1365-313x.2005.02433.x
|View full text |Cite
|
Sign up to set email alerts
|

Repression of light signaling by Arabidopsis SPA1 involves post‐translational regulation of HFR1 protein accumulation

Abstract: SummaryArabidopsis uses two major classes of photoreceptors to mediate seedling de-etiolation. The cryptochromes (cry1 and cry2) absorb blue/ultraviolet-A light, whereas the phytochromes (phyA-phyE) predominantly regulate responses to red/far-red light. Arabidopsis COP1 represses light signaling by acting as an E3 ubiquitin ligase in the nucleus, and is responsible for targeted degradation of a number of photomorphogenesispromoting factors, including HY5, LAF1, phyA, and HFR1. Distinct light signaling pathways… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
88
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 76 publications
6
88
0
Order By: Relevance
“…Because spa and cop1 mutations also interact genetically it is hypothesized that SPA proteins function in concert with COP1 to ubiquitinate activators of the light response (Hoecker and Quail, 2001;Laubinger et al, 2004;Saijo et al, 2003). In agreement with this idea, HY5 and HFR1 protein levels are increased in spa1 mutant seedlings (Saijo et al, 2003;Yang et al, 2005a). Moreover, recombinant SPA1 altered the in vitro ubiquitin ligase activity of COP1 (Saijo et al, 2003;Seo et al, 2003).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Because spa and cop1 mutations also interact genetically it is hypothesized that SPA proteins function in concert with COP1 to ubiquitinate activators of the light response (Hoecker and Quail, 2001;Laubinger et al, 2004;Saijo et al, 2003). In agreement with this idea, HY5 and HFR1 protein levels are increased in spa1 mutant seedlings (Saijo et al, 2003;Yang et al, 2005a). Moreover, recombinant SPA1 altered the in vitro ubiquitin ligase activity of COP1 (Saijo et al, 2003;Seo et al, 2003).…”
Section: Introductionsupporting
confidence: 68%
“…It has been shown previously that SPA proteins act in concert with another repressor of light signaling, the ubiquitin ligase COP1, which ubiquitinates light signaling activators in dark-grown seedlings (Hoecker and Quail, 2001;Laubinger et al, 2004;Saijo et al, 2003;Seo et al, 2003;Yang et al, 2005a). Here, we have demonstrated that SPA proteins are, moreover, required for photoperiodic flowering in the facultative LD plant Arabidopsis.…”
Section: Discussionmentioning
confidence: 54%
“…HFR1 also interacts with the myb transcription factor LONG AFTER FAR-RED LIGHT1, which is involved in FR-HIR (Jang et al, 2007). Furthermore, HFR1 interacts with COP1 and SPA1, leading to its ubiquitin-dependent degradation in darkness, thereby abolishing photomorphogenesis (Duek et al, 2004;Jang et al, 2005;Yang et al, 2005aYang et al, , 2005b. HFR1 phosphorylation is promoted by light, and the protein is stabilized under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that COP1-mediated degradation of HY5, LAF1, and HFR1 is stimulated by SUPPRES-SOR OF PHYTOCHROME A1 (SPA1), a negative regulator of photomorphogenesis (Saijo et al, 2003;Seo et al, 2003Seo et al, , 2004Jang et al, 2005;Yang and Wang, 2006). SPA1 has been shown to physically interact with COP1, HY5, and HFR1 and is required for COP1-mediated degradation of HY5 and HFR1 (Hoecker and Quail, 2001;Saijo et al, 2003;Yang et al, 2005).…”
mentioning
confidence: 99%
“…Among them, COP1 is a well-studied master repressor of photomorphogenesis (Deng and Quail, 1992). COP1 functions as an E3 ubiquitin ligase in the nucleus and is responsible for the degradation of a group of photomorphogenic growth-promoting factors such as HY5, LAF1, HFR1, and phyA and thereby desensitizes light signal transduction (Osterlund et al, 2000;Saijo et al, 2003;Seo et al, 2003Seo et al, , 2004Yang et al, 2005). Furthermore, it has been demonstrated that COP1-mediated degradation of HY5, LAF1, and HFR1 is stimulated by SUPPRES-SOR OF PHYTOCHROME A1 (SPA1), a negative regulator of photomorphogenesis (Saijo et al, 2003;Seo et al, 2003Seo et al, , 2004Jang et al, 2005;Yang and Wang, 2006).…”
mentioning
confidence: 99%